Subjetividades docentes en tiempos de la excelencia educativa - Plata Santos, María Eugenia (Colombian Applied Linguistics Journal, 2018)
This article purposes to analyze constitutive and constituent elements of the subjectivities of teachers in the context of government practices that promote “teacher excellence”. For this purpose, this text is concerned with the questioning of these discourses and their effects on the constitution of subjectivities, it also arises how to recognize characteristics or powers that can make alternative practices of subjectivation possible. The article begins with a critical and reflexive approach on the conditions of teacher training and exercise within the framework of current policies of educational quality within the current political economy of human capital. Something that in the educative applies with the concept of “Educational Excellence”. In a second moment, explains the contributions of theoretical order on the notions of subject-subjectivation-subjectivity, based on the approaches of authors like Foucault, (1995, 2005, 2012), Lazzarato, (2006, 2010), De Sousa Santos, (2000) and Deleuze, (1995), among others. With these two aspects it is expected to perform a critical analysis of the elements that make up the teaching subjectivities today, making visible possible lines of flight, which would allow desujetion processes.